Literature Review: of The Effect of Plant Extracts That Contain Alkaloids on The Histopathology of Diabetic Rat Kidneys - Fauzan, Muhamad Adam; Widayanti, Etty; Royhan, Aan (Junior Medical Journal, 2025)
Introduction: Diabetes mellitus (DM) is a chronic disease that occurs when the pancreas cannot produce enough insulin or the body cannot use the insulin made effectively. Antidiabetic drugs usually have side effects such as nausea and anorexia. Therefore, alternative medicines such as herbal medicines are needed. Plants have phytochemical compounds and secondary metabolites such as phenols, alkaloids, steroids, glycosides, flavonoids and certain pigments. Alkaloids are secondary metabolite compounds in many plant and animal tissues and have the most nitrogen atoms. This study aims to determine the research results on the effects of giving herbal plant extracts on the histopathological picture of the kidneys of diabetes mellitus rats. Methods: This study uses the Literature Review method with a narrative literature review type. Data collection techniques in this study were carried out by searching for data through the database on Google Scholar. Four journals were obtained as research sources based on the exclusion and inclusion criteria. Results: Plants that contain alkaloids are effective in improving kidney conditions. Alkaloids are antioxidant compounds that can provide nephron cell protection and kidney repair in glomerular endothelial cells, increasing the glomerular filtration rate (GFR). Increased GFR will reduce creatinine and uranium levels in the blood. Conclusion: Plant extracts that contain alkaloids can repair kidney damage in diabetes mellitus rats. According to the Islamic view, alkaloids can improve the condition of damaged kidneys, so it is allowed to consume because plants have many benefits that are very useful for human health that can be used as natural medicines.